A Life without Hunger: The Ups (and Downs) to Modulating Melanocortin-3 Receptor Signaling - Butler, Andrew A.; Girardet, Clemence; Mavrikaki, Maria; Trevaskis, James L.; Macarthur, Heather; Marks, Daniel L.; Farr, Susan A. (Frontiers in Neuroscience, 2017)
Melanocortin neurons conserve body mass in hyper- or hypo-caloric conditions by conveying signals from nutrient sensors into areas of the brain governing appetite and metabolism. In mice, melanocortin-3 receptor (MC3R) deletion alters nutrient partitioning independently of hyperphagia, promoting accumulation of fat over muscle mass. Enhanced rhythms in insulin and insulin-responsive metabolic genes during hypocaloric feeding suggest partial insulin resistance and enhanced lipogenesis. However, exactly where and how MC3Rs affect metabolic control to alter nutrient partitioning is not known. The behavioral phenotypes exhibited by MC3R-deficient mice suggest a contextual role in appetite control. Homeostatic responses to hypocaloric conditioning involving increased expression of appetite-stimulating (orexigenic) neuropeptides, binge-feeding, food anticipatory activity, entrainment to nutrient availability and enhanced feeding-related motivational responses are compromised with MC3R-deficiency. Rescuing Mc3r transcription in hypothalamic and limbic neurons improves appetitive responses during hypocaloric conditioning, suggesting orexigenic functions. Rescuing hypothalamic MC3Rs also restores responses of fasting-responsive hypothalamic orexigenic neurons in hypocaloric conditions, suggesting actions that sensitize fasting-responsive neurons to signals from nutrient sensors. MC3R signaling in ventromedial hypothalamic SF1(+ve) neurons improves metabolic control, but does not restore appetitive responses or nutrient partitioning. In summary, desensitization of fasting-responsive orexigenic neurons may underlie attenuated appetitive responses of MC3R-deficient mice in hypocaloric situations. The orexigenic actions of hypothalamic and limbic MC3Rs are contextual, and do not affect feeding behavior in ad libitum conditions or nutrient partitioning. Further studies are needed to identify the specific location(s) of MC3Rs controlling appetitive responses and partitioning of nutrients between fat and lean tissues.